Hubungan Karakteristik Pasien Kolelitiasis terhadap Lamanya Perawatan di Rumah Sakit Umum Cut Meutia - Muhammad Nawawi; Muhammad Sayuti; Adi Rizka (Lembaga Pengembangan Kinerja Dosen, 2026)
Cholelithiasis is the formation of hardened bile deposits within the gallbladder due to an imbalance in the chemical composition of bile, which can cause symptoms ranging from abdominal pain to serious complications such as cholecystitis, biliary obstruction, and gallbladder infection. This study aimed to determine the relationship between patient characteristics and the length of hospital stay in cholelithiasis patients at Cut Meutia General Hospital. This study used an analytical observational design with a cross-sectional approach and a retrospective study, employing a total sampling technique with 50 patients. The results showed that most patients were female (52.0%), with the largest age group being late elderly (28.0%). The most common surgical technique was laparoscopic cholecystectomy (42.0%), and the majority of patients received surgical management (60.0%). Bivariate analysis using the Chi-Square test showed significant relationships between age (p=0.000), gender (p=0.044), surgical technique (p=0.029), and management (p=0.045) with the length of hospital stay in cholelithiasis patients. The conclusion of this study is that there is a relationship between patient characteristics and the length of hospital stay in cholelithiasis patients.